İBN SİNA VE İBN RÜŞD FELSEFESİNDE ALLAH'NIN SIFATLARININ KARŞILAŞTIRILMASI - CANPOLAT, GÜLTEN DOĞAN (Fırat Üniveristesi, 2006)
SummaryMaster ThesisComparisan of the titles of Allah at İbn Sûnâ and İbn Rüşd PhilosophyGülten CANPOLATFırat UniversityThe Institute of Social SciencesAnd Postgraduate Studyy in Philosophy And Relegion Scienceİslâm Philosoph Science2006; Page: VIII-90The subject of Allah's titles is a subject measured very much. Philosophy,Moslem Theology, Moslem Mysticism etc. Sciences take into consideration this subject.According to İbn Sûnâ, Allah knows that he creates universe himself but doesn'twant it. Knowledge of Allah, at the same time, it is the meaning of his creation. Mealy,at this stuation, there is no need to any resolution and force title any more. At this timephilosophers don't repudiate Allah's resolution title, they interpret him in the form ofharmony with his knowledge title.İbn Rüşd, similar to these philosophers, believes that acceptace of titles isunbecoming to monotheism belief. According to him, if we accept an individual andadditional titles, we'll repudiate the term of Vacibu'l Vücud. A person who accept thiskind of situation is faulty.To believe in existance and unique of Allah is possible with knowing him withhis titles and names carefully. Faith in Allah is the base of all religions. The need ofbelieve in Allah, supported by him and worship, exists in human beings. This senseburns with human and it improves in every step.Key Words: Allah, title, İslam Philosophy, obligatory existence, Vacibu'l Vücud.

SummaryMaster ThesisComparisan of the titles of Allah at İbn Sûnâ and İbn Rüşd PhilosophyGülten CANPOLATFırat UniversityThe Institute of Social SciencesAnd Postgraduate Studyy in Philosophy And Relegion Scienceİslâm Philosoph Science2006; Page: VIII-90The subject of Allah?s titles is a subject measured very much. Philosophy,Moslem Theology, Moslem Mysticism etc. Sciences take into consideration this subject.According to İbn Sûnâ, Allah knows that he creates universe himself but doesn?twant it. Knowledge of Allah, at the same time, it is the meaning of his creation. Mealy,at this stuation, there is no need to any resolution and force title any more. At this timephilosophers don?t repudiate Allah?s resolution title, they interpret him in the form ofharmony with his knowledge title.İbn Rüşd, similar to these philosophers, believes that acceptace of titles isunbecoming to monotheism belief. According to him, if we accept an individual andadditional titles, we?ll repudiate the term of Vacibu?l Vücud. A person who accept thiskind of situation is faulty.To believe in existance and unique of Allah is possible with knowing him withhis titles and names carefully. Faith in Allah is the base of all religions. The need ofbelieve in Allah, supported by him and worship, exists in human beings. This senseburns with human and it improves in every step.Key Words: Allah, title, İslam Philosophy, obligatory existence, Vacibu?l Vücud.
Comparisan of the titles of Allah at İbn Sina and İbn Rüşd philosophy
Keywords: Din; Felsefe